Annual Plan West Bengal 2002-2003 - Planning Commission (Planning Commission, 2002)
Against the background of worldwide recessionary trend and all pervasive effects of globalisation the task of preparation of the Annual Plan of the State Government functioning within the framework of the Constitution is, indeed, a critical job. It is more so in the context of the dominant role of the market forces in the present dispensation. the paradigm shift in policies has left little scope for the planning to play its role as it earlier did. We do not, however, consider planning to be merely a conventional exercise but, on the contrary, think it to be a testament that reflects our commitment for all round development of the State and its people. It, in fact, encapsulates the vision that constantly inspires and propels man to make this good earth a better place to live in-a vision that adds meaning to our social existence.
Development and Planning Department Government of West Bengal